MEMS and Microfluidics in Healthcare Devices and Applications Perspectives - Guha, Koushik; Dutta, Gorachand; Biswas, Arindam; Srinivasa Rao, K. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
The book introduces the research significance of biomedical instrumentation and discusses micro-fabrication techniques utilized for biomedical devices. This book primarily focuses on the reader enlightenment on MEMS medical devices by introducing all the diagnostic devices and treatment tools at one place. The book covers in-depth technical works and general introductions to the devices such that the book can reach technical as well as non-technical readers.
N/MEMS Biosensors: An Introduction -- Lab-on-a-Chip Technology in Health Care -- A Review on Recent Trends in the Segregation of Red Blood Cells Using Microfluidic Devices -- A Road Map to Paper-based Microfluidics towards affordable disease detection -- Critical Review and Exploration on Micro pumps for Microfluidic Delivery -- Fabrication Techniques & Materials for Bio-MEMS.-In-silico analysis of expandable radiofrequency electrode for ablation of hepatic tumors -- Lab-on-Chip Electrochemical Biosensor for Rheumatoid Arthritis -- Transdermal Injection with Microneedle Devices in Healthcare Sector: Materials, Challenging Fabrication Methodologies and its Limitations -- An economical and efficient method for the fabrication of spiral micromixer -- Damping Estimation and Analysis for High Performance Inertial MEMS for Early Detection of Neurological disorders during Pregnancy -- Affinity biosensing: Modeling of Adsorption Kinetics and Fluctuation Dynamics.
Keywords: Microtechnology; Microelectromechanical systems; Microfluidics; Biomedical engineering; Microsystems and MEMS; Microfluidics; Biomedical Devices and Instrumentation